Magnetic resonance imaging findings of the lumbar spine in elite horseback riders: Correlations with back pain, body mass index, trunk/leg-length coefficient, and riding discipline - Kraft, C. N.; Pennekamp, P. H.; Becker, U.; Young, M.; Diedrich, O.; Lüring, C.; von Falkenhausen, M. (The American Journal of Sports Medicine, 2009)
Most orthopaedic problems experienced by competitive horseback riders are related to pain in the lower back, hip joint, and hamstring muscles. Riders—especially, show jumpers—are frequently hampered in their performance because of lumbar pain. To date, there has been no research into lumbar disk degeneration in elite competitive riders.